Salt-wedge estuary's response to rising sea level, reduced discharge, and Nature-Based Solution - Verri, Giorgia; De Lorenzis, Alessandro; Santos da Costa, Vladimir; Sorolla, Albert; Löchner, Adrian; Ribot, Miquel; Marti, Eugenia; DelGado, Sara Castelar; Coppini, Giovanni; Pinardi, Nadia (Frontiers in Climate, 2024)
Vulnerable estuaries face resilience challenges against climate-induced salinization. This study examines the Po di Goro estuary in the Northern Adriatic Sea using an innovative modeling approach. It assesses the effectiveness of a Nature-Based Solution in reducing the threat of salt-wedge intrusion. An intermediate-complexity numerical model is considered, leveraging its low computational cost, which is suitable for climate projections, along with robust physics encompassing the main estuarine processes. Two centennial climate experiments covering 1991–2100 are proposed following a mechanistic modeling approach to understand the compound effects of sea level rise and river discharge changes. The first experiment is a full forcing experiment. The second experiment uses the same model but removes the sea level rise as an input forcing. A third experiment, referred to as the Digital Twin Experiment, assesses the effectiveness of a location-specific Nature-Based Solution. This experiment specifically examines the impact of reducing salt levels in the water by using a halophyte plant along the estuary. The results show that, in a future climate change scenario, the salt-wedge intrusion increases. This response is due to the non-linear combination of reduced river discharge and the local sea level rise. The discharge decrease acts as the main driver in the mid-term future (i.e., 2050–2080). In the long-term future (i.e., 2080–2100), the local sea level rise becomes more relevant as the discharge trend is expected to be null. The salt-wedge intrusion in the Po di Goro is projected to increase up to 63% annually (120% in summertime). Additionally, the river mouth salinity could rise by 27% annually (69% in summertime) in the long-term future (2081–2100). The halophyte plant, Atriplex portulaciodes, proposed as Nature-Based Solution, could reduce salt-wedge intrusion in the Po di Goro by up to 16% annually (22% in summer) in the long-term future. In the short-term future, this Nature-Based Solution may be effective enough to counteract the salt increase.